Curriculum and Learning for Climate Action Toward an SDG 4.7 Roadmap for Systems Change - Iyengar, Radhika (IBE on Curriculum, Learning, and Assessment, 2021)
Curriculum and Learning for Climate Action offers researchers, practitioners, donors, and decisionmakers insights into entry points for education systems change needed to reorient human society's relationship with our planetary systems.; Readership: All interested in Sustainability, International Education, Environmental Education will find this book useful. This includes researchers, students, policy makers, global practitioners, as well as think tanks, and donors.